Mapping The Discourse: Scientometric Analysis Of Affordable Housing Research Trends - Nor Suzylah Sohaimi; Nur Aili Hanim Hanafiah; Azhani Abd Manaf; Tülay Zıvalı (Journal of Contemporary Urban Affairs, 2024)
Non-Indexed Publication